COMMUNICATION IN ORGANIZATIONS : A NETWORK OF COMPLEX RELATIONSHIPS - Janisleydis Rodriguez Alarcon (Journal of Management Small and Medium Enterprises (SMEs), 2015)
Communication in organizations is a very important for its development and survival element insociety. It is one that provides for exchanges of information, knowledge, signs and symbols amongits different audiences, also including the environment as a determinant. Various channels andforms of communication which states in this regard, can find among them upward communication,descent, vertical and horizontal. Keywords: Communication, organization, organizational communication.